2022
DOI: 10.2147/ijgm.s294906
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Oxygenation in Patients with Acute Respiratory Failure: Current Perspectives

Abstract: Purpose of Review High-flow nasal oxygen and noninvasive ventilation are two alternative strategies to standard oxygen in the management of acute respiratory failure. Discussion Although high-flow nasal oxygen has gained major popularity in ICUs due to its simplicity of application, good comfort for patients, efficiency in improving oxygenation and promising results in patients with acute hypoxemic respiratory failure, further large clinical trials are needed to confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In conclusion, we observed that HFNC -used as escalation therapy for untreatable hypoxia during COT or NIV/CPAP -significantly increased arterial oxygenation without causing hypercapnia in ARF patients admitted to a geriatric non-intensive ward. HFNC is better tolerated than NIV, assures continuous ventilation without interruptions, does not compromise normal nutrition and oral hydration and allows patients to continue communicating with others, thereby reducing the risk of dehydration, malnutrition and delirium [3][4][5]18]. It should also be mentioned that, compared to NIV, HFNC decreased inspiratory effort in type 1 ARF, thus mitigating the risk of self-inflicted lung injury [5], and this may have contributed to the lower mortality observed during HFNC [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In conclusion, we observed that HFNC -used as escalation therapy for untreatable hypoxia during COT or NIV/CPAP -significantly increased arterial oxygenation without causing hypercapnia in ARF patients admitted to a geriatric non-intensive ward. HFNC is better tolerated than NIV, assures continuous ventilation without interruptions, does not compromise normal nutrition and oral hydration and allows patients to continue communicating with others, thereby reducing the risk of dehydration, malnutrition and delirium [3][4][5]18]. It should also be mentioned that, compared to NIV, HFNC decreased inspiratory effort in type 1 ARF, thus mitigating the risk of self-inflicted lung injury [5], and this may have contributed to the lower mortality observed during HFNC [4].…”
Section: Discussionmentioning
confidence: 99%
“…High flow nasal cannula oxygen therapy (HFNC) is another type of non-invasive respiratory support [3][4][5]. A very high flow of heated and humidified gas mixture (oxygen plus room air) is administered through soft nasal prongs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations